Indywidualizacja nauczania języków obcych młodzieży z dysleksją a automatyzacja ich procesu uczenia się - Jaworska, Mariola (Papers in Linguistics, 2019)
The aim of this article is to provide an analysis of conditions and perspectives of teaching a foreign language to students with developmental dyslexia, following the rules of autonomising teaching. The first part of the article discusses developmental dyslexia, which is considered to be a reflection of individual learning differences. In the second part, teaching young people with dyslexia is considered in the context of autonomisation of their learning process. Further analyses are preceded by characterising the category of “autonomisation of learning”, including such basic terms as “autonomy” “semi-autonomy” “autonomisation”. The subsequent part refers to developing dyslexic students’ autonomy, since stimulating students to take responsibility for their own learning and development has been found important and effective. As opening the process of teaching students is believed to be the most basic condition of autonomisation of learning, the final part is concerned with assumptions and possibilities of implementing open teaching in educating dyslectic learners, with a special focus on open forms of learning.